7-Hydroxycoumarin Attenuates Colistin-Induced Kidney Injury in Mice Through the Decreased Level of Histone Deacetylase 1 and the Activation of Nrf2 Signaling Pathway - Wang, Jian; Ishfaq, Muhammad; Fan, Qianqian; Chen, Chunli; Li, Jichang (Frontiers in Pharmacology, 2020)
Colistin has been considered as the last line of defense against Gram-negative bacterial infections, however, the potential nephrotoxicity limited its clinical use. 7-Hydroxycoumarin (7-HC) possesses many beneﬁcial pharmacological activities. This study aimed to investigate the nephroprotective effects of 7-HC against colistin-induced kidney injury. In-vivo experiments showed that 7-HC alleviated kidney injury induced by colistin, as indicated by lower levels of serum neutrophil gelatinase-associated lipocalin, blood urea nitrogen and creatinine levels. Both in vivo and in vitro results demonstrated that 7-HC alleviated oxidative stress and apoptosis induced by colistin, as shown by decreased malondialdehyde levels, decreased caspase-3 and caspase-9 activities, and increased superoxide dismutase and catalase activities. We also found that colistin significantly induced histone deacetylase (HDAC) 1 expression that deacetylated histone 3 at Lys27 acetylation (H3K27AC) of Nrf2 promoter region and hence inhibiting Nrf2 signaling. 7-HC treatment restored histone acetylation at the Nrf2 promoter region and hence promoted Nrf2 expression. These results suggested that 7-HC alleviates colistin-induced renal injury and this eﬀect was achieved by enhancement of renal antioxidant capacity with the decreased level of HDAC1 and the activation of Nrf2 signaling pathway.